Status and Contamination Level of the Wastewater of Gebeng Industrial Estate, Pahang, Malaysia - Islam, Mir Sujaul; Sobahan, Md Abdus; Karim, Md Abdul (Bangladesh Botanical Society, 2015)
The pH of the water of the studied stations was slightly acidic to neutral, while EC was included within recommended standard. The contamination intensity, pollution level, classification of water indicated that the wastewater having higher contamination level, especially, BOD, COD, NH3-N, PO4, Pb, Cd, Cr, Cu, Co, Ni and Hg concentration were high in all samples with lower DO value. The high COD content indicated that the wastewater of Gebeng area contains higher wastes. However, the results were differed on the basis of seasons and types of industries. It was also found that Pb and Hg concentrations were higher in wet season in comparison to dry, while Cd, Co, Cr, Cu, Zn, Ni, Ba and As concentrations were higher in dry season in comparison to wet. All sampling sites were categorized as highly polluted.